CORRELATION OF OUTLOOK AND INTERNAL BELIEFS OF LAW ENFORCEMENT SUBJECTS IN THE CONTEST OF THE IMPLEMENTATION OF THEIR DISCRETIONARY AUTHORITIES - Vandzhurak, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: the purpose of this study is to consider the definition of the concept and nature of the formation of the worldview and inner conviction of law enforcement subjects when they make procedural decisions and to investigate the coverage in the scientific literature of certain aspects of the influence of the worldview on the inner conviction in general and in the context of possible negative consequences in particular. Research methods: the author used the methods of analysis, synthesis and generalization, with the help of which the bibliography of the issue was worked out, and the methods of deductive-logical analysis and inductive generalization and analogy were used to substantiate the results and formulate the conclusions of the conducted research. Results: the conducted research established that, in contrast to innovations in accordance with modern legal realities, an element of an almost unlimited range of subjective possibilities remains in law, in particular procedural law, which is expressed in the ability of a subject with discretionary powers to make decisions based on internal conviction, influence which, not least, has his worldview. Discussion: considering the distrust of society in the legalized right of the subjects of making procedural decisions to make them on the basis of their inner conviction, research on the subject of establishing and researching the factors that form such a conviction is very relevant. Separately, the concepts of worldview and inner conviction are sufficiently disclosed in the scientific work, but no works on the topic of their relationship, and even more so the influence of the former on the latter, either by foreign authors or by Ukrainian researchers, were found. Along with this, on the basis of the literature analyzed by the author, it was found that any inner conviction is primarily based on a person’s value and outlook orientations, which are formed during his life, and especially in childhood and adolescence. Therefore, faced in his professional activity with a problem regarding which the subject of law enforcement has already formed a certain view, the latter, when making a procedural decision, may, contrary to the actual circumstances of the case and the evidence available in it, take a different position, which in turn will have negative consequences for the rule of law and will thereby worsen citizens’ trust in law enforcement and judicial bodies. The practical significance of this study is that the obtained results can form the basis of changes in the current legislation regarding the evaluation of candidates for positions with discretionary powers, paying more careful attention to their value beliefs and worldview orientations.